Glass fiber-reinforced polyester composite fatigue crack monitoring using acoustic emission - Gholizadeh, Samira (2015)
Acoustic Emission (AE) is an elastic stress wave which is produced by a quick release of the energy through a material. There are many reasons that result in AE such as deformation of the material, crack initiation and growth of cracks. Only a little study has investigated about damage assessment in glass fiber reinforced polyester composite, and some other studies considered about one or two AE signal parameters with pattern recognition. AE basic parameters have not been widely used to detect the onset of damage in composite materials. This study was done to apply AE technique by using basic parameters for detecting onset of glass fiber reinforced polyester composite materials damage and validate this technique using actual AE data from fatigue growth. Tensile test was done on 3 specimens of glass fiber reinforced polyester composite to find out the percentage of applied stress. 15 specimens were used for the fatigue test with 40%, 45%, 50%, 55%, and 60% of ultimate tensile strength (UTS) as a stress level. A cyclic tension-tension loading was applied to the samples, during the test, AE sensor was attached to the center of the specimens and AE signal parameters were generated from the specimens during the test. The discussion showed when crack propagated in materials; AE signal parameters such as energy, amplitude, number of hits, as well as correlation of two basic parameter such as amplitude versus duration was were analyzed to find out crack growth behavior in different stage of testing in early time of testing, middle and near fracture zone. Therefore from the trend of the AE signal parameters, failure of material such as matrix cracking between 40 dB - 60 dB ofamplitude, fiber debonding 60 dB - 65 dB, fiber pull out between 65 dB - 85 dB and fiber breakage between 85 dB - 100 dB were observed. The high degree correlation between AE signal parameters such as energy and number of hits, between number of cycles to failure as well as applied stress with R2 = 91% and R2 = 92% in the composite material presented that AE basic parameter can be used for detecting the onset of damage as it can record from initial cracks and also crack propagation at different time of service at different stress level.